KONTEN FLEXING BERSEDEKAH DALAM PERSPEKTIF HUKUM ISLAM (KAJIAN TAFSIR AHKAM) - Husna, Nihayatul (IAINU Kebumen Prodi IAT, 2023)
Recently, there has been a lot of flexing charity content on social media such as Instagram, Facebook, YouTube and TikTok. Flexing is done to achieve various goals, including getting praise, attracting sympathy, or creating a good impression for other people to trust them. Judging from Islamic teachings, flexing can be said to be an act of showing off which is part of arrogance, self-pride, or an attitude of riya. Meanwhile, giving alms in the Qur'an is permitted openly or hiddenly. So it can be said that not all alms that are created as content or shown to the public are part of flexing in the sense of riya. This research is qualitative in nature using library research research methods. The reference sources for this research are books or literature that have a correlation with flexing giving alms and tafsir books that are based on Fiqh or Ahkam interpretations. The method used in this research is the thematic interpretation method, namely analyzing verses related to almsgiving and flexing (riya) in the Al-Qur'an. The results of this research are; 1) The content of alms is not necessarily part of flexing/riya, 2) The content of giving alms or showing alms is permitted in Islam as long as alms are obligatory such as zakat, if alms are sunnah then it is better to hide them, 3) The content of giving alms can be said to be flexing/riya if the intention is and the aim is to boast, be arrogant, and want to be seen by many people in order to receive praise, this is what is prohibited by Islamic teachings.